(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research is motivated by the problems faced by the Moria Hammer congregation futsal team, which lies in the basic technique of dribbling the ball, this is because every training schedule is still monotonous. The goal that the author wants to achieve in this study is to determine whether there is an effect of box drill training with rings and bounding with rings on improving dribbling in futsal games on the Moria Hammer congregation team. This type of research uses a quantitative approach with a preliminary experimental method. The population and sample in this study were 66 people. And the sample taken amounted to 30 people using the t-test analysis technique. Based on the results of the analysis conducted, it was found that (1) there is an increase in dribbling agility in futsal players of the moria hammer congregation following box drill training with rings by 4.59 seconds and hypothesis testing where the value of tcount = 9.520> ttable = 2.145, accepted, (2) there is an increase in dribbling agility in futsal players of the moria hammer congregation following bounding training with rings by 7.55 seconds and hypothesis testing where tcount = 6, 850> t table 2,145, accepted (3) there is no difference in the influence between box drill training with rings and bounding with rings on the agility of dribbling futsal games on the moria hammer congregation futsal team ", with these results the tcount value of 0.310 is smaller than the ttable value of 2.145 or (0.310> 2.145) with a value of d. bn-1 or 15-1 = 14). bn-1 or 15-1 = 14, at a significant level a = 0.05.